A new giant hyracoid from the Limeworks Quarry, Makapansgat, Potgietersrus - Kitching, J. W. (Bernard Price Institute for Palaeontological Research, 1965)
In this paper a new genus and species of giant hyrax from the Limeworks Quarry, Makapansgat, Potgietersrus, is described. This new hyrax is 1 1/2 times larger than the largest specimen thus far extracted from any Pleistocene deposit in Africa. The name Cigantohyrax maguirei gen. et sp. nov., is proposed.
Main article
Keywords: Hyracoid; Limeworks Quarry; Makapansgat; South Africa